MicroRNAs as efficient biomarkers in high-grade gliomas - Barciszewska, Anna-Maria (Folia Neuropathologica, 2016)
High-grade gliomas are the most aggressive and devastating brain neoplasms. Therefore much effort is put on understanding their background as well as development of new effective diagnostic and therapeutic methods. However, until now the genetic only approach has not provided a satisfactory answer. Recently, it has been shown that the epigenetic issue is important for high-grade gliomas’ development and progression. Out of many epigenetic mechanisms, as DNA methylation, histone methylation and acetylation, especially microRNAs showed to be deeply involved in the carcinogenesis process. MicroRNAs are short non-coding RNAs. They are new candidates for human disease biomarkers due to their simple identification. MicroRNAs are stable in tissue and body fluids, what makes them very prospective non-invasive, blood-based biomarkers. There is a lot of data showing that various profiles of serum microRNAs are linked to numerous neoplastic processes, indicating that microRNAs can be really a new class of biomarkers for human diseases.